2017
DOI: 10.3390/fermentation3010010
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Carboxylic Acid Production by Megasphaera elsdenii from Glucose and Lignocellulosic Hydrolysate

Abstract: Volatile fatty acids (VFAs) can be readily produced from many anaerobic microbes and subsequently utilized as precursors to renewable biofuels and biochemicals. Megasphaera elsdenii represents a promising host for production of VFAs, butyric acid (BA) and hexanoic acid (HA). However, due to the toxicity of these acids, product removal via an extractive fermentation system is required to achieve high titers and productivities. Here, we examine multiple aspects of extractive separations to produce BA and HA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…This study showed that in the absence of pertraction but with amines included, the extraction efficiency only increased by 1.4-fold, while with pertraction the increase was significantly higher. In another study with in situ separation using pertraction, butyric acid and hexanoic acid productivity was found to increase by at least 3-fold while using pertractive fermentation when compared to batch fermentation [141]. These studies indicated that oleyl alcohol with trioctylamine as the extractant was found to be less inhibitory to the microbial culture during pertractive fermentation when compared to octanol-trihexylamine extractant.…”
Section: Separation Using Solvent Extractionmentioning
confidence: 94%
“…This study showed that in the absence of pertraction but with amines included, the extraction efficiency only increased by 1.4-fold, while with pertraction the increase was significantly higher. In another study with in situ separation using pertraction, butyric acid and hexanoic acid productivity was found to increase by at least 3-fold while using pertractive fermentation when compared to batch fermentation [141]. These studies indicated that oleyl alcohol with trioctylamine as the extractant was found to be less inhibitory to the microbial culture during pertractive fermentation when compared to octanol-trihexylamine extractant.…”
Section: Separation Using Solvent Extractionmentioning
confidence: 94%
“…P. fermentans LDH clusters with proteins from organisms that consume lactate anaerobically ( Fig. 11 ), including two bacteria known to convert lactate to MCFA, Ruminococcaeae CPB6 and Megasphaera elsdenii (5, 7), and with the LDH from A. woodii that uses electron confurcation to couple lactate and ferredoxin oxidation with NAD + reduction to overcome the thermodynamic bottleneck of lactate oxidation (27). Pairwise correlation analyses of transcript abundance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In situ extraction occurs with a direct contact between the cells and the extraction phase: (a) two‐phase partitioning bioreactors or (b) solvent‐impregnated particles dispersed in bioconversion medium or with an indirect contact: (c) using immobilized cells in the bioconversion broth; or (d) using membrane‐based extraction inside the bioreactor . In‐stream extraction occurs with direct contact: (e) pumping bioconversion broth to a column packed with solvent‐impregnated particles or indirect contact: (f) membrane‐based extraction outside the bioreactor; or (g) introducing a microfiltration unit to separate the biocatalyst from broth before contact …”
Section: Introductionmentioning
confidence: 99%
“…18,19 In-stream extraction occurs with direct contact: (e) pumping bioconversion broth to a column packed with solvent-impregnated particles 20 or indirect contact: (f ) membrane-based extraction outside the bioreactor 21,22 ; or (g) introducing a microfiltration unit to separate the biocatalyst from broth before contact. 23,24 accumulation in the medium can be avoided by progressively supplying glycerol. 7 This pathway has the advantage that no other by-products are present, which simplifies further purification of the desired product.…”
Section: Introductionmentioning
confidence: 99%